Distinguishing Sexual Harassment From Attempted Rape In The Judicial Practice Of Uzbekistan: Issues Of Legal Qualification And Interpretation - Tursunmurodov Komron Turgun ogli (Peerian Journals Publishing, 2025)
This article analyzes recent judicial practice in Uzbekistan concerning the classification of acts as sexual harassment. Following the adoption of Law No. ZRU-829 in 2023, sexual harassment was officially recognized as an administrative offence. The article reviews several significant cases from 2024 in which actions such as sending sexually explicit messages via social media, initiating sexual activity, inappropriate touching with sexual intent, exposing genitalia, and declarations of love were classified as sexual harassment. A special focus is placed on the legal distinction between sexual harassment and attempted rape. Although these offences may share certain features, the article emphasizes that the presence or absence of violence in the offender's actions constitutes a critical criterion for differentiation. A comparative table of legal and factual elements is proposed to guide judicial assessment of such cases.
Keywords: sexual harassment; attempted rape; administrative offence